The Influence of Transformational Leadership, Incentives, and Rewards on Job Satisfaction and Employee Performance in the Pharmaceutical Industry - Setiawan, Hengky; Cahyadi, Lukman; Nurhasanah , Nina; Saulina, Arop Ria (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of transformational leadership, incentives, and rewards on job satisfaction and employee performance in the pharmaceutical industry. It aims to analyze both direct and mediating effects of job satisfaction. Using a quantitative approach, data were collected from 122 employees through questionnaires and analyzed using SEM-PLS. The results indicate that incentives, rewards, and transformational leadership do not directly affect employee performance but significantly influence job satisfaction, which in turn positively affects performance. Job satisfaction fully mediates the relationship between incentives, rewards, and employee performance. The findings highlight the strategic importance of enhancing job satisfaction to improve organizational performance. Keywords: Transformational Leadership; Incentives; Rewards; Job Satisfaction; Employee Performance; Pharmaceutical Industry; SEM-PLS; Mediation Effect